Furan-based materials for organic electronics - Chan, Rachel Hui Xin (Nanyang Technological University, 2024)
This project focuses on the chemical synthesis and characterization of conjugated furan compounds, for the development of novel molecules for organic electronic applications. Furan was chosen as the starting compound as it is obtainable from sustainable sources. Through organic chemical synthesis methodologies, the target furan-based molecules were developed and tested for their properties. This was to determine if they could be used for the intended organic electronic applications. The target molecules were (2Z,2’Z)-2,2’-(1,4-phenylene)bis(3(furan-2-yl)acrylonitrile) for R1, and (2Z,2’Z)-2,2’-(1,4-phenylene)bis(3-(5(hydroxymethyl)furan-2-yl)acrylonitrile) for R3. The characterization techniques used on the target molecules include NMR spectroscopy, FTIR spectroscopy, UV-Vis, PL spectroscopy, TGA and DSC.